PENGARUH INTERVENSI AKSI BERGIZI TERHADAP TINGKAT KEPATUHAN MINUM TABLET TAMBAH DARAH (FE) PADA REMAJA PUTRI KELAS VIII DI SMPN 2 SUKODONO KECAMATAN SUKODONO KABUPATEN LUMAJANG - Hevandari, Dwi (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Compliance of female adolescents in consuming iron supplement tablets is one of the indicators of the success of anemia prevention and control programs among adolescent girls. The aim of this study is to determine the influence of nutritional action intervention on the compliance rate of iron supplement tablet consumption among 8th grade female adolescents at SMPN 2 Sukodono, Sukodono Sub-district, Lumajang Regency. The research design used in this study was a one-group pretest-posttest design. The sample consisted of 74 respondents selected through total sampling technique, and the statistical test used was the Wilcoxon test. The results of the study revealed that the majority of the respondents had low compliance rates before the implementation of nutritional action intervention, with 44 respondents (59.5%) exhibiting low compliance. However, after the intervention, the majority of the respondents showed a high compliance rate, with 69 respondents (93.2%) demonstrating high compliance, while 5 respondents (6.8%) still exhibited low compliance. The analysis using the Wilcoxon test yielded a p-value of 0.000, indicating a significant influence of the implementation of the nutritional action intervention on the compliance rate of iron supplement tablet consumption among 8th grade female adolescents at SMPN 2 Sukodono, Sukodono Sub-district, Lumajang Regency. It is recommended to encourage collaboration among nurses, teachers, and parents in the implementation of the program. Close cooperation among all stakeholders can strengthen the program implementation and improve the compliance rate of female adolescents.